Facing the Hungry Tide : Climate Change, Livelihood Threats, and Household Responses in Coastal Bangladesh - Dasgupta, Susmita; Hossain, Md. Moqbul; Huq, Mainul; Wheeler, David (World Bank Group, Washington, DC, 2015)
This paper quantifies the impact of inundation risk and salinization on the family structure and economic welfare of coastal households in Bangladesh. These households are already on the "front line" of climate change, so their adaptation presages the future for hundreds of millions of families worldwide who will face similar threats by 2100. The analysis is based on a household decision model that relates spatial deployment of working-age, migration-capable members to inundation and salinization threats. The analysis uses appropriate estimation techniques, including adjustments for spatial autocorrelation, and finds that households subject to high inundation and salinization threats have significantly higher out-migration rates for working-age adults (particularly males), dependency ratios, and poverty incidence than their counterparts in non-threatened areas. The findings indicate that the critical zone for inundation risk lies within four kilometers of the coast, with attenuated impacts for coastal-zone households at higher elevations. The results paint a sobering picture of life at the coastal margin for Bangladeshi households threatened by inundation and salinization, particularly households that are relatively isolated from market centers. They respond by "hollowing out," as economic necessity drives more working-age adults to seek outside earnings. Those left behind face a far greater likelihood of extreme poverty than their counterparts in less-threatened areas. The powerful results for market access, coupled with previous findings on salinity and road maintenance, suggest that infrastructure investment may offer a promising option. Road improvements that reduce travel times for isolated settlements compensate them for an increase in salinity. Thus, road improvement may warrant particular attention as an attractive adaptation investment in coastal Bangladesh.